Universal Health Coverage for Inclusive and Sustainable Development : Country Summary Report for Vietnam - Barroy, Helene; Jarawan, Eva; Bales, Sarah (World Bank Group, Washington, DC, 2014)
Vietnam is regarded as a development success story. Political and economic reforms ( Doi Moi ) launched at the end of the 1980s have transformed the country from one of the poorest in the world to a lower middle-income country in a quarter century, with per capita income of $1,130 (World Bank, 2013). Over the past 10 years, Vietnam has seen average annual economic growth of nearly 8 percent. Poverty tumbled from 58 percent in 1993 to 12 percent in 2009. Economic development and innovative policy interventions led to steep gains in health outcomes and access to health care, although large disparities persist between the rich and poor, and between poorer and better-off regions (Vietnam General Statistics Office 2011b). Infant mortality declined from 30 to 16 per 100,000 live births, and under-five mortality rates from 42 to 25 per 100,000 live births, between 2001 and 2009 (Vietnam General Statistics Office 2011a, 2011c). Vietnam has shown strong political commitment toward universal health coverage (UHC), making it a national goal for 2014. A major challenge lies now in expanding coverage to the non-covered population (64 percent had coverage in 2012) while addressing the model s financial sustainability.